An examination of the decision-making skill perceptions of third grade and fourth grade students in primary school - BAYSAL, ZELİHA NURDAN (My University, 2021)
Our life is shaped by the decisions we make. Our experiences show how these decisions affect our lives. Decision-making is a thinking skill and can be taught over the process. Primary school is an educational institution where the foundations of students’ future experiences are laid and where students overcome problems by taking part in decisions. The experiences acquired in those ages undoubtedly impact their future experiences. A review of the literature reveals a need for decision-making studies on primary school students in Turkey. The purpose of this study is to examine the decision-making skill perception of third and fourth grade students in terms of several variables. Students\" gender, age, grade level and their teachers\" and parents\", participation in the decision were covered as variables in this study using the survey model, a quantitative research method. The population of the study comprises Istanbul province while five schools based in the European and Asian sides of Istanbul constitute the sampling. The easily accessible sampling method was used in the selection of sampling. \"The Marmara Decision-Making Skill Perception Scale for Primary School Students\" was used for data collection. The scale is a four-point Likert-type scale with 5 factors and 17 items. According to the results, students’ decision-making skill perception is at a medium level. Based on gender, students’ decision-making skill perception differs significantly in favor of the male students, although there is no significant difference in terms of age, grade, and whether or not the student’s opinion is asked in decision-making processes at home and school. Keywords: Thinking skill, decision-making, primary schoo
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; İlköğretim; Social Sciences and Humanities; Education; Elementary School Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Social Sciences & Humanities; Thinking skill; decision-making; primary school; : Düşünme becerisi; karar verme; ilkokul